Transfer Pricing Mechanisms and International Tax Management Strategies in Multinational Companies in the Digital Economy Era - Geby Citra Ananda; Khaira Amalia Fachrudin (International Journal of Management, Economic and Accounting, 2026)
The development of the digital economy has led to significant changes in the expansion and operational activities of multinational corporations (MNCs), which have implications for transfer pricing management and international tax management strategies. This study aims to analyze how transfer pricing mechanisms are utilized and what tax strategies are implemented by multinational corporations in the digital era, particularly in the technology and data-driven services sectors. The research method employs a qualitative approach using case study techniques and in-depth interviews with tax practitioners. The findings identify that companies maximize the use of intangible assets and digital licenses to optimize tax burdens through transfer pricing planning. This study also discusses challenges in international tax regulation, as well as policy recommendations that are adaptive to the phenomenon of economic digitalization.